2010
DOI: 10.1016/j.dam.2010.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Disjoint dominating and total dominating sets in graphs

Abstract: a b s t r a c tIt has been shown [M.A. Henning, J. Southey, A note on graphs with disjoint dominating and total dominating sets, Ars Combin. 89 (2008) 159-162] that every connected graph with minimum degree at least two that is not a cycle on five vertices has a dominating set D and a total dominating set T which are disjoint. We characterize such graphs for which D ∪ T necessarily contains all vertices of the graph and that have no induced cycle on five vertices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 7 publications
0
12
0
Order By: Relevance
“…We will also need the result that every graph has two disjoint sets, one total dominating and one “half‐total” dominating: Theorem () If G is a graph with minimum degree at least two, then, except for the 5‐cycle, G has disjoint dominating and total dominating sets.…”
Section: Claw‐free Graphsmentioning
confidence: 99%
See 1 more Smart Citation
“…We will also need the result that every graph has two disjoint sets, one total dominating and one “half‐total” dominating: Theorem () If G is a graph with minimum degree at least two, then, except for the 5‐cycle, G has disjoint dominating and total dominating sets.…”
Section: Claw‐free Graphsmentioning
confidence: 99%
“…Theorem 15. ( [15]) If is a graph with minimum degree at least , then, except for the 5-cycle, has disjoint dominating and total dominating sets.…”
Section: Claw-free Graphsmentioning
confidence: 99%
“…In contrast to that, Zelinka [14,15] observed that no minimum degree condition is sufficient for the existence of three disjoint dominating sets or of two disjoint total dominating sets. In [9] Henning and Southey proved the following result which is somehow located between Ore's positive and Zelinka's negative observation.…”
Section: Introductionmentioning
confidence: 91%
“…Theorem 1 (Henning and Southey [9]) If G is a graph of minimum degree at least 2 such that no component of G is a chordless cycle of length 5, then V (G) can be partitioned into a dominating set D and a total dominating set T .…”
Section: Introductionmentioning
confidence: 99%
“…Among these is a paper by Henning and Southey [16] in which they prove that any connected graph having minimum degree at least two, and not a cycle on 5 vertices, possesses a dominating set and a disjoint total dominating set (a dominating set S for which every node in V , rather than V − S, has a neighbor in S). It would be interesting to see if the algorithms in this paper can be modified to find disjoint dominating sets of different types.…”
Section: Conclusion and Suggested Problemsmentioning
confidence: 99%